The Impact of Human Resource Management Strategies on Organizational Performance in the Creative Industry Sector - Shanaya, Shanty (Generasi Sains Indonesia, 2025)
This study explores the impact of Human Resource Management (HRM) practices on organizational performance in the creative industry sector, focusing on key HRM practices such as recruitment, training and development, performance management, and compensation. Using a quantitative approach, the research employed multiple regression, correlation analysis, and ANOVA tests to assess the influence of these practices on organizational outcomes, including innovation, productivity, and creativity. The results revealed that training and development had the strongest positive impact on organizational performance, highlighting the importance of continuous skill development in fostering innovation. Recruitment practices also significantly influenced organizational performance, particularly in innovation, while compensation had a less pronounced effect, emphasizing the importance of intrinsic motivation in the creative sector. Additionally, organizational size was found to influence HRM effectiveness, with larger organizations reporting better HRM practices. This study fills a gap in the literature by focusing on the creative industry, offering both theoretical and practical contributions to HRM research, and providing actionable insights for HR practitioners in creative organizations. The findings underscore the need for HRM systems that foster creativity, attract talent, and align employee efforts with organizational goals.